Effect of planting time and variety on growth and yield attributes of tomato in semi-arid conditions of Rajasthan (IASH Indian Journal of Arid Horticulture, 2026)
During the experimentation studied the effect of five planting time and three varieties of tomato during winter season of 2019-2020, 2020-21 and 2021-22. During the experiment three tomato variety viz. WS-1299 (V1 ), Krishna (V2 ) and Bavandar (V3 ) were studied with five different dates of planting viz. 30 December (D1 ), 15 December (D2 ), 15 January (D3 ), 30 January (D4 ) and 15 February (D5 ). In which the yield of tomato was significantly affected by different sowing dates and verities. Among varieties and planting dates the variety Bavander (V3 ) planted on 15 January (D3 ) produced significantly higher number of fruits/ plant (39.70), fruit weight (83.25 g) and fruit yield (727.20 q/ ha) with the maximum B:C ratio (4.05).